2006
DOI: 10.1089/neu.2006.23.853
|View full text |Cite
|
Sign up to set email alerts
|

Dural Repair Reduces Connective Tissue Scar Invasion and Cystic Cavity Formation after Acute Spinal Cord Laceration Injury in Adult Rats

Abstract: This study examined whether duraplasty after acute cervical laceration spinal cord injury (SCI) in a rat model could (1) improve cerebrospinal fluid (CSF) circulation adjacent to the injury; (2) minimize connective tissue scarring; and (3) reduce post-traumatic inflammation and cystic cavitation. Following a transverse dural/arachnoid incision and C5-6 dorsal spinal hemisection, a 5-mm2 cadaveric dura mater allograft was placed over the lesion and fixed with fibrin glue (n=12). Control animals received an iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 33 publications
0
52
1
Order By: Relevance
“…Cavitation is induced by apoptosis of cells, inflammatory response and tissue degradation, which results in functional deficits after SCI [1]. Reduction of the cavity size is often involved in the functional recovery of CNS injury by various therapies such as duraplasty and graft of skin-derived precursor cells [27,28]. In this study, GM-CSF remarkably reduced the size of cavity and protected spinal cord tissues from severe damage at 3 weeks after SCI.…”
Section: Discussionmentioning
confidence: 63%
“…Cavitation is induced by apoptosis of cells, inflammatory response and tissue degradation, which results in functional deficits after SCI [1]. Reduction of the cavity size is often involved in the functional recovery of CNS injury by various therapies such as duraplasty and graft of skin-derived precursor cells [27,28]. In this study, GM-CSF remarkably reduced the size of cavity and protected spinal cord tissues from severe damage at 3 weeks after SCI.…”
Section: Discussionmentioning
confidence: 63%
“…6,15 In addition, a reduction in cavity size is often involved in functional recovery after CNS injury. 3,13 It is possible that the reduced glial scar formation in Groups 3 and 4 resulted in better maintenance of the integrity of the axon fibers 4 weeks after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Iannotti et al studied the histological response to a lacerationtype spinal cord injury in a rodent model 27 . They reported that, relative to animals left with a large dural defect, animals that had received a dural allograft had decreased lesional macrophage accumulation, cystic cavitation, and scarring as well as improved cerebrospinal fluid flow.…”
Section: Discussionmentioning
confidence: 99%